Tourism Development Potential and Strategy at Molino Beach (Matano Lake) Sorowako Village, East Luwu Regency, South Sulawesi - Rahman, Yaumyta Nur; Mulyadi, Yadi; Achmad, Mahmud (Journal of Cultural Analysis and Social Change, 2026)
Molino Beach is a tourist destination located in the Matano Lake area, Sorowako Village, East Luwu Regency, South Sulawesi. This area has high potential for ecotourism-based water tourism, but has not been optimally managed due to minimal government attention. This study aims to analyze the Tourism Suitability Index (IKW) parameters and formulate a strategy for sustainable ecotourism-based area development. The method used is a descriptive method with an IKW calculation approach, SWOT analysis, and IFE and EFE matrix analysis. The results show that Molino Beach is categorized as Very Suitable (S1) for ecotourism activities with an IKW value of 88.75%. The SWOT analysis identified various internal and external factors that influence area management, while the results of the IFE and EFE analysis showed values of 2.672 and 2.962, respectively. Based on the IE Matrix, the development position is in quadrant V (hold and maintain), which indicates the need for a strategy to strengthen existing potential accompanied by a measurable and sustainable growth direction.